Pengembangan Bahan Ajar Berbasis Higher Order Thinking Skill (HOTS) - Putri Pinta Permata Bate’e; Umbu Citra Kasih Zebua; Edieli Nazara; Arozatulo Bawamemewi (Departement of Mathematics Education, 2023)
Development of learning materials based on higher order thinking skills using research and development (R & D) methods. This research was conducted in Class VIII of SMP Negeri 1 Botomuzoi. The purpose of this study was to determine the suitability of HOTS-based book teaching materials for fiction and non-fiction material as well as the quality of teaching materials. Based on the research conducted and the formulation of the problem and research objectives, the authors draw several conclusions, including: (1). Based on product validation, it appears that HOTS-based fiction and non-fiction teaching materials are very suitable to function as teaching materials at SMP Negeri 1 Botomuzoi (2). Based on the results of student survey data processing, it was found that HOTS-based fiction and non-fiction teaching materials fulfilled the practical requirements, namely the teaching materials produced were practical when used as teaching materials at SMP Negeri 1 Botomuzoi.